1203 Blockade of the mechanistic target of rapamycin elicits rapid and lasting improvement of disease activity through restraining pro-inflammatory T cell lineage specification in patients with active SLE. (14th December 2022) - Lai, Zhi-Wei; Kelly, Ryan; Winans, Thomas; Marchena, Ivan; Shadakshari, Ashwini; Yu, Julie; Dawood, Maha; Garcia, Ricardo; Tily, Hajra; Francis, Lisa; Faraone, Stephen V; Phillips, Paul E; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) patients exhibit proinflammatory lineage development in the immune system that has been attributed to mechanistic target of rapamycin (mTOR) activation. Moreover, mTOR activation has also been shown in resident cells of tissues affected by end-organ damage. Therefore, safety, tolerance, and efficacy of rapamycin were examined in prospective 1 and retrospective biomarker-driven clinical trials 2, 3 . Methods: 40 patients having active disease and unresponsive or intolerant to conventional medications were enrolled in a prospective study 1 . Sirolimus was started at 2 mg/day with dosage adjusted to tolerance and 6-15 ng/ml trough levels. Disease activity was evaluated by BILAG, SLEDAI, and prednisone use over 12 months. Blood samples of 56 matched healthy subjects were obtained as controls for immunometabolic outcomes monitored at each visit. The effects of sirolimus was also investigated retrospectively in 73 patients with or without nephritis 2 and 187 patients with lupus nephritis 3 . Results: As primary clinical efficacy endpoint, SLEDAI disease activity scores were reduced over 12 months in 16/29 patients (55%). 19/29 patients (65.5%) met criteria for SLE Responder Index (SRI). Arthritis, rash, pyuria, and hypocomplementemia improved among SLEDAI components, while cardiopulmonary, musculoskeletal, mucocutaneous, and vasculitis BILAG organ-domain scores also declined. Prednisone use diminished from 24.3±4.7 mg/day to 7.2±2.3 mg/day (p<0.0009). Sirolimus expanded CD4 + CD25 + FoxP3 + Tregs and CD8 + memory T cells and inhibited IL-4 and IL-17 production by CD4 + and CD4 - CD8 - double-negative T cells after 12 months. CD8 + memory T cells were selectively expanded in SRI- responders 1 . In 12 patients of 73 patients who had lupus nephritis, proteinuria (p=0.0287), hematuria (p=0.0232), anti- DNA antibody levels (p=0.0028) and steroid use were reduced (p=0.0200). In the non-renal cohort of 61 patients, anti-DNA antibody levels (p=0.0332) and steroid use were reduced (p=0.0163). Both in the renal and non-renal cohorts, C3 (renal p=0.0070; non-renal p=0.0021) and C4 complement levels were increased (renal p=0.0063; non-renal p=0.0042) Adverse effects of mouth sores (2/73), headaches (1/73), and gastrointestinal discomfort were noted in a minority of patients (6/73). Sirolimus was only discontinued in two of 73 patients due to headache and recurrent infections, respectively 2 . The retrospective study of 187 LN patients evaluated mTOR activation in renal tissue of 187 LN patients in comparison to 20 diabetic nephropathy (DN) patients, 10 minimal change disease (MCD) patients, and 10 normal controls (NCs) 3 . mTOR complexes 1 and 2 (mTORC1/2) were activated in podocytes, mesangial cells, endothelial cells and tubular epithelial cells of LN patients as compared with those with MCD or NC. The glomerular mTORC1 activation was higher in LN patients compared with DN patients. mTORC1, but not mTORC2, activation strongly correlated with crescent formation, interstitial inflammation and fibrosis and serum albumin, complement C3, and proteinuria. mTORC1 activation was identified as a prognostic marker in LN patients. Conclusions: These studies suggests that sirolimus is well tolerated and exerts long-term therapeutic efficacy in controlling renal and non-renal manifestations of SLE. Renal mTORC1 activation may predict clinical prognosis and therapeutic response to sirolimus in patients with LN. Acknowledgements: This work was supported in part by an Investigator-Initiated Research Grant P0468X1-4470/WS1234172 from Pfizer and grants AI 048079, AI 072648, and AI 122176 from the National Institutes of Health and the Central New York Community Foundation. Trial Registration: Prospective Study of Rapamycin for the Treatment of SLE; ClinicalTrials.gov Identifier: NCT00779194 . Treatment trial of SLE with N-acetylcysteine; ClinicalTrials.gov identifier: NCT00775476 . Lay summary: Rapamycin, also called as sirolimus, has been newly identified as a new treatment with promising clinical effectiveness and well-defined mechanism of active in patients with moderate to severe SLE. References: Lai, Z. et al. Sirolimus in patients with clinically active systemic lupus erythematosus resistant to, or intolerant of, conventional medications: a single-arm, open-label, phase 1/2 trial. Lancet 2018;391 : 1186- 1196 Piranavan, P., and Perl, A. Improvement of renal and non-renal SLE outcome measures on sirolimus therapy - A 21-year follow-up study of 73 patients. Clin. Immunol. 2021;229: 108781 Mao, Z. et al. Renal mTORC1 activation is associated with disease activity and prognosis in lupus nephritis. Rheumatology, 2022; keac037 Perl, A. Mechanistic Target of Rapamycin Pathway Activation in Rheumatic Diseases. Nat. Rev. Rheumatol. 2016; 12, 169–182 Yoshida, S. et al. Redox Regulates Mammalian Target of Rapamycin Complex 1 (mTORC1) Activity by Modulating the TSC1/TSC2-Rheb GTPase Pathway. J. Biol. Chem. 2011;286, 32651–32660 Lai, Z.-W. et al. N-acetylcysteine reduces disease activity by blocking mTOR in T cells of lupus patients. Arthritis Rheum. 2012;64, 2937–2946 Perl, A. et al. Comprehensive metabolome analyses reveal N-acetylcysteine-responsive accumulation of kynurenine in systemic lupus erythematosus: implications for activation of the mechanistic target of rapamycin. Metabolomics 2015;11, 1157–1174